Pushover analysis of fiber-reinforced polymer-strengthened masonry - Ghiassi, Bahman (2019)
[Excerpt] 17.1 Introduction Fiber-reinforced polymers (FRPs) have been extensively used for seismic strengthening of existing concrete and masonry structures. The ease of application and high strength-to-weight ratio of these composites have made them an interesting solution for strengthening purposes.[...]